WATER QUALITY OF FISHING LOCATION OF SEPATUNG FISH (Pristolepis grootii) AT KELEKAR RIVER, OGAN ILIR REGENCY OF SOUTH SUMATERA - Muslim, Muslim (AQUASAINS, 2020)
This study aims to determine the parameters of water quality at the fishing locations of the sepatung fish (Pristolepis grootii). Water quality is very influenced by environmental conditions. Kelekar River is one of the rivers located in the area of the flooded swamp area. The water quality characteristics of this river are very influenced by the condition of the surrounding swamps. Based on water acidity (pH) parameters, the quality of river water tends to be acidic, but the sepatung fish (P grootii) can live, grow and develop in this habitat. Water quality in natural waters habitats h can be used as a reference in the maintenance of fish in aquaculture media.